2011
DOI: 10.1089/gyn.2009.0086
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy for Cornual Ectopic Pregnancy

Abstract: Background: Ectopic pregnancy rarely occurs in the uterine cornu. When it does, it exposes the affected patient to the risk of death from rupture with intra-abdominal bleeding. Its surgical management is difficult. The primary modalities for treating this condition are surgery in the form of laparotomy and methotrexate administration. They both have advantages and potential shortcomings. An alternative option is operative laparoscopy, which may be preferable to these other approaches under certain circumstance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…There is a paucity of long‐term fertility data following laparoscopic cornual resection using the Endo GIA ™ Stapler system as none of the authors of the previous 11 published cases had reported follow‐up reviews of their patients. For completion, we have included a picture taken during elective CS showing the cornual stump in our patient who had a previous right laparoscopic cornual resection using Endo GIA™ Universal Stapler two years prior (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a paucity of long‐term fertility data following laparoscopic cornual resection using the Endo GIA ™ Stapler system as none of the authors of the previous 11 published cases had reported follow‐up reviews of their patients. For completion, we have included a picture taken during elective CS showing the cornual stump in our patient who had a previous right laparoscopic cornual resection using Endo GIA™ Universal Stapler two years prior (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic cornual resection (cornuectomy) using a stapling device, Multifire Endo GIA ™ Stapler (Medtronic, Watford, UK), was first described by Sergent et al . in 2003, and in total so far, 11 cases have been published in the literature . The Multifire Endo GIA ™ Stapler is an automatic stapler with disposable reloadable cartridges (2, 2.5 or 3.5 mm), which places two triple‐staggered rows of titanium mini‐staples and simultaneously divides the tissue between the two rows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation